Psycholinguistics and Metacognition Effect in Verbal Language Communication Ability on Practical Teaching of Physics Education Students - Rozelin, Diana; Sukarno, Sukarno; Muhaimin, Muhaimin (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2024)
This study aimed to determine and describe the influence of psycholinguistics and metacognition on the ability of physics education students to use verbal language in the learning process. Quantitative research is used to measure the level of influence between variables, and then the case study is used to determine the sample. Based on the data, it could be concluded that the ability of psycholinguistics had a positive correlation with language skills, with a correlation of 0.924 and a significance value (2-tailed) of 0.000 <0.05. Thus, it could be understood that there was a positive correlation between psycholinguistics toward language skills with a very strong correlation category. The correlation between metacognition and language skills was 0.874 with a significance value (2-tailed) of 0.000 < 0.05. Therefore, this article argues that the ability of psycholinguistics and metacognition, so the language skills of physics students in carrying out physics learning would be better. This meant that the two variables affected the verbal language skills in learning physics together and not separately. Because language skills are related to metacognitive abilities, including intellectual abilities, teachers need to consider the use of verbal language in the classroom for the cognitive development of students. To achieve this, a psycholinguistic skill development program was needed for physics education students and other prospective teacher students; they could use verbal language in both the declarative, imperative, and interrogative aspects appropriately and accurately.